Gambaran Pengetahuan Ibu Nifas Tentang Perawatan Tali Pusat - Ningtias, Meysifa; Achyar, Khamidah; Kusuma, Inggar Ratna (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The newborn mortality rate is one of the indicators used to describe the health status of the community. According to the World Health Organization (WHO), in 2015 the infant mortality rate in the world reached 54 per 1000 live births, in developing countries the infant mortality rate was relatively high and very varied, reaching 11-68 per 1000 live births, while in Southeast Asia the IMR reached 39 per 1000 live births, of which 21% are caused by infection (WHO, 2016). The reason is because there is still a lack of knowledge of mothers in caring for newborns, especially for preventing infection of the umbilical cord. This study aims to describe the knowledge of postpartum mothers regarding umbilical cord care in newborns. This type of research is in the form of a literature review with a descriptive method. This literature search is through publications in two databases, namely Pubmed and Google Scholar. The search strategy method for obtaining journals uses the keywords